A Scholar in Foreign Warfare: Characterizing Dislocation in For Whom the Bell Tolls - M Irfan Zamzami (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
This paper is aimed at analyzing literary devices used to establish the sense of dislocation in Ernest Hemingway’s For Whom the Bell Tolls. The research study uses objective approach to literature using E.M. Forster’s analytical tool and nomenclature to novel that is formulated in Aspects of the Novel. As the results demonstrated, dislocation is established through: 1) juxtaposition of the character’s history and 2) Hispanicization of the main character’s identity. The character’s “history” emphasizes the contrast of the main character’s life prior to the narrated events. Contradictions are apparent in the main character’s internal dialectic between being a scholar and becoming a soldier. The second approach to dislocation is caused by linguistic and cultural barrier barrier between Anglophone and Hispanophone characters demonstrated through deliberate Hispanicization. Keywords: dislocation; novel; Ernest Hemingway; character analysis.